2003
DOI: 10.1023/a:1022856715409
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Carbon assimilation in maize follows the C(4) mechanism. This requires the tissue-specific and light-induced expression of a set of different genes involved in CO(2) fixation as well as adaptations in the leaf anatomy including a reduced distance between vascular bundles compared to C(3) plants. However, several maize tissues exist with larger bundle distances and there is significant evidence that CO(2) fixation follows the C(3) mechanism in these tissues. We isolated maize C(3) and C(4) tissues and quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The RBCS multigene family consists of 2–22 members, depending on the species (Sasanuma, 2001; Spreitzer, 2003). The number of expressing members and transcript abundance within the RBCS multigene family have been investigated in different tissues, under different environments, and/or during tissue development in some plant species including tomato (Wanner and Gruissem, 1991; Meier et al , 1995), Lemna gibba (Silverthorne and Tobin, 1990; Silverthorne et al , 1990), Arabidopsis (Dedonder et al , 1993; Cheng et al , 1998; Yoon et al , 2001), French bean (Knight and Jenkins, 1992; Sawbridge et al , 1996), maize (Ewing et al , 1998; Hahnen et al , 2003), wheat (Galili et al , 1998), rice (Suzuki et al , 2009 b ), and Eucalyptus (Suzuki et al , 2010). In rice, it has been demonstrated that four out of the five RBCS genes are highly expressed in leaf blades and that the total RBCS mRNA level is highly correlated with Rubisco content at their maxima irrespective of tissues and growth stages (Suzuki et al , 2009 a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The RBCS multigene family consists of 2–22 members, depending on the species (Sasanuma, 2001; Spreitzer, 2003). The number of expressing members and transcript abundance within the RBCS multigene family have been investigated in different tissues, under different environments, and/or during tissue development in some plant species including tomato (Wanner and Gruissem, 1991; Meier et al , 1995), Lemna gibba (Silverthorne and Tobin, 1990; Silverthorne et al , 1990), Arabidopsis (Dedonder et al , 1993; Cheng et al , 1998; Yoon et al , 2001), French bean (Knight and Jenkins, 1992; Sawbridge et al , 1996), maize (Ewing et al , 1998; Hahnen et al , 2003), wheat (Galili et al , 1998), rice (Suzuki et al , 2009 b ), and Eucalyptus (Suzuki et al , 2010). In rice, it has been demonstrated that four out of the five RBCS genes are highly expressed in leaf blades and that the total RBCS mRNA level is highly correlated with Rubisco content at their maxima irrespective of tissues and growth stages (Suzuki et al , 2009 a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…For corn bract (CB), as a typical agricultural waste, open burning is a usual disposal method and occurs more frequently in grain-producing regions, with increasing crop yields in China . However, the burning has been considered as an important source of carbonaceous species.…”
Section: Introductionmentioning
confidence: 99%